Potential of native entomopathogenic nematodes for the control of brown marmorated stink bug Halyomorpha halys in Georgia. Issue 9 (1st September 2020) - Burjanadze, Medea; Gorgadze, Oleg; De Luca, Francesca; Troccoli, Alberto; Lortkipanidze, Manana; Kharabadze, Natalia; Arjevanidze, Mariami; Fanelli, Elena; Tarasco, Eustachio
ABSTRACT: The potential of native entomopathogenic nematodes for the control of the brown marmorated stink bug Halyomorpha halys was evaluated in experimental trials in Georgia. Two Georgian strains of Heterorhabditis bacteriophora (HRB, GEO) and Steinernema borjomiense and two Italian strains of H. bacteriophora (HRB, IT) and S. apuliae were used in laboratory assays (22°C and 80% RH) at concentrations of 1000, 500 and 200 infective juveniles (IJs) per adult H. halys . The mortality of tested insects was estimated from the third day after treatment. Differences in mortality of the tested insect were observed between Georgian and Italian strains. At the highest concentration (1000 IJs/adult), mortality (%) of H. halys induced by Georgian strains HRB and S. borjomiense was 53.3 and 40, respectively, at 500 IJs/adult 40 and 33.3, and at 200 IJs/adult 33.3 and 13.3, respectively. Italian strains HRB (IT) and S. apuliae proved more suppressive against the tested insects, with mortality rates of 95.5 and 60, 93.3 and 40 and 73.3 and 33.2%, at concentrations of 1000, 500 and 200 IJs/adult of H. halys, respectively . The present study provides further insights in selection of promising EPN strains to be used against this harmful insect pest, although further studies to test their efficacy under field conditions are needed.